Maximum upper esophageal sphincter (UES) admittance: a non‐specific marker of UES dysfunction. Issue 2 (6th November 2015) - Cock, C.; Besanko, L.; Kritas, S.; Burgstad, C. M.; Thompson, A.; Heddle, R.; Fraser, R. J. L.; Omari, T. I.
Abstract: Background: Assessment of upper esophageal sphincter (UES) motility is challenging, as functionally, UES relaxation and opening are distinct. We studied novel parameters, UES admittance (inverse of nadir impedance), and 0.2‐s integrated relaxation pressure (IRP), in patients with cricopharyngeal bar (CPB) and motor neuron disease (MND), as predictors of UES dysfunction. Methods: Sixty‐six healthy subjects ( n = 50 controls 20–80 years; n = 16 elderly >80 years), 11 patients with CPB (51–83 years) and 16 with MND (58–91 years) were studied using pharyngeal high‐resolution impedance manometry. Subjects received 5 × 5 mL liquid (L) and viscous (V) boluses. Admittance and IRP were compared by age and between groups. A p < 0.05 was considered significant. Key Results: In healthy subjects, admittance was reduced (L: p = 0.005 and V: p = 0.04) and the IRP higher with liquids ( p = 0.02) in older age. Admittance was reduced in MND compared to both healthy groups (Young: p < 0.0001 for both, Elderly L: p < 0.0001 and V: p = 0.009) and CPB with liquid ( p = 0.001). Only liquid showed a higher IRP in MND patients compared to controls ( p = 0.03), but was similar to healthy elderly and CPB patients. Only admittance differentiated younger controls from CPB (L: p = 0.0002 and V: p < 0.0001), with no differences in either parameter between CPB and elderly subjects. Conclusions & Inferences: The effects of aging and pathology were better discriminated by UES maximum admittance, demonstrating greater statistical confidence across bolus consistencies as compared to 0.2‐s IRP. Maximum admittance may be a clinically useful determinate of UES dysfunction. Abstract : Novel parameters UES admittance and 0.2‐s integrated relaxation pressure were measured in patients with pharyngeal motor abnormalities (MND and CP bar), and compared to healthy controls. Admittance was reduced in older age, and in patients with CPB or MND, in line with deteriorating swallowing function. Upper esophageal sphincter maximum admittance is a non‐specific marker of UES opening dysfunction.